2021
DOI: 10.1002/fsn3.2190
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial, anti‐inflammatory, analgesic, and hemostatic activities of Acanthopanax trifoliatus (L.) merr

Abstract: Acanthopanax trifoliatus (L.) Merr (AT) is a medicinal and edible plant with high nutritional value. The biological activity of A. trifoliatus (L.) Merr and its basis for injury treatment are explored in this paper. AT was ethanol‐extracted then refined separately with petroleum ether, chloroform, ethyl acetate, and n‐butanol. Active ingredients were analyzed, and anti‐bacterial, anti‐inflammatory, analgesic, and hemostatic effects were explored. Petroleum ether layer (PEL) extract produced the strongest antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…With an increase in 5-CQA concentration, the inhibition rate of the inflammatory factor IL-6 increased correspondingly ( Gao et al, 2020 ). Acanthopanax senticosus extract contains 3-CQA, 3,5-DiCQA, and 4,5-DiCQA, which have strong anti-inflammatory effects ( Chen et al, 2021 ). 4-CQA exerts anti-inflammatory effects by reducing oxidative stress during the inflammatory response ( Zhao et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…With an increase in 5-CQA concentration, the inhibition rate of the inflammatory factor IL-6 increased correspondingly ( Gao et al, 2020 ). Acanthopanax senticosus extract contains 3-CQA, 3,5-DiCQA, and 4,5-DiCQA, which have strong anti-inflammatory effects ( Chen et al, 2021 ). 4-CQA exerts anti-inflammatory effects by reducing oxidative stress during the inflammatory response ( Zhao et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that ATRB has good anti-inflammatory and antioxidant effects. Researchers found that treatment with the water extract of ATRB can prolong the exhaustive exercise time of rats with chronic swimming stress, and 10 phenolic acids were isolated and identified from the water extract, among which chlorogenic acid and (+)-syringaresinol-di-O-beta-D-glucoside were the main components (Chen et al, 2021; Wang et al, 2015; Xiao et al, 2011). The main effective components of ATRB are phenolic acids (Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It can work to strengthen the body and mind and has the efcacy of nourishing Qi, strengthening the spleen, nourishing the kidney, and soothing the nerves [3]. Te primary chemical constituents of A. senticosus include polyphenols [4], polysaccharides [5], glycosides [6], and lignans, which have good pharmacological activities to regulating immune function [7], antifatigue efect [8], antioxidant activity [9], and anti-infammatory properties [10]. Polyphenols are secondary plant metabolites found in traditional Chinese medicine with potential efects on health and are also the general term for plant components with several phenolic hydroxyl groups in the molecular structure, including polyphenols, tannins, phenolic acids, and anthocyanins [11].…”
Section: Introductionmentioning
confidence: 99%